2010
DOI: 10.1007/s00213-010-1778-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered thermoregulation via sensitization of A1 adenosine receptors in dietary-restricted rats

Abstract: Rationale Evidence links longevity to dietary restriction (DR). A decrease in body temperature (Tb) is thought to contribute to enhanced longevity because lower Tb reduces oxidative metabolism and oxidative stress. It is as yet unclear how DR decreases Tb. Objective Here, we test the hypothesis that prolonged DR decreases Tb by sensitizing adenosine A1 receptors (A1AR) and adenosine-induced cooling. Methods and results Sprague–Dawley rats were dietary restricted using an every-other-day feeding protocol. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Mechanisms involved in induction of hypothermia are under investigation. Results from our studies have shown that DR-induced hypothermia is due to adenosine sensitization (Jinka et al, 2010). Our results have demonstrated that intraperitoneal administration of CHA (0.5mg/kg) in DR-sensitized rats induced a significant cooling undetected in ad libitum (AL) rats.…”
Section: Significance Of Adenosine On Dietary Restriction Induced Hypmentioning
confidence: 58%
See 3 more Smart Citations
“…Mechanisms involved in induction of hypothermia are under investigation. Results from our studies have shown that DR-induced hypothermia is due to adenosine sensitization (Jinka et al, 2010). Our results have demonstrated that intraperitoneal administration of CHA (0.5mg/kg) in DR-sensitized rats induced a significant cooling undetected in ad libitum (AL) rats.…”
Section: Significance Of Adenosine On Dietary Restriction Induced Hypmentioning
confidence: 58%
“…These results also suggest that a torpid like effect is seen with CHA-induced hypothermia in DR rats. However, it is not known from these studies as to how the heart responds to this CHA-induced hypothermia in DR rats (Jinka et al, 2010).…”
Section: Previous Studies and Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Major surgery is required to implant the intraperitoneal transmitters, but the data obtained show unequivocal patterns of hibernation 6,2528 . If hibernating animals are housed at ambient temperatures of ≥20 °C, then transponders such as the IPTT-300 (Bio Medic Data Systems, city, state) can be used to monitor body temperature with a telemetry system (DAS-6000; Bio Medic Data Systems) 29,30 . These transponders can be implanted subcutaneously between the scapula without surgery but may not be reliable below 21.4 °C (ref.…”
Section: Reductionmentioning
confidence: 99%